Perancangan dan Pengujian Mesin Pengayak Pasir Halus Tipe Rotary Berkapasitas 20 kg/jam - Hudaya, Adam Aryadana; Wulandari, Diah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Sand sieving in small to medium-scale construction projects is still widely done manually, resulting in inconsistent output, time inefficiency, and increased labor demand. This study aims to design and test a prototype of an automatic rotary-type sand sieving machine with a capacity of 20 kg/hour to improve operational effectiveness and efficiency. The machine features a rotating cylindrical drum driven by a 220V electric motor with a maximum power of 0.5 HP. The engineering design method was employed through an experimental approach involving needs analysis, conceptual design, fabrication, and performance testing. Key components include a 30 cm diameter, 70 cm long drum, two-stage pulley-belt transmission system, and an 8â€“10 mm mesh wire screen. Test results show that the machine operates stably at a 5Â° inclination with a drum speed of 87.5 RPM. Sieving 2 kg of mixed sand yielded 1.57 kg of fine sand in 40 seconds, achieving a sieving efficiency of 78.5%. The portable and modular design facilitates maintenance and is suitable for supporting sand processing activities in small and medium-scale construction sectors.